A History of Rowley-Wittenham. Deserted Medieval Village and Lost Parish - Rogerson, Andrew (Medieval Settlement Research, 2023)
Overwhelmingly concerned with documentary sources, this lavishly illustrated small book leaves the presentation of the archaeological evidence for the deserted village of Rowley-Wittenham until page 73. Both understanding and interpreting the historical record are rendered more difficult by a boundary which shifts between Wiltshire and Somerset, the mutability of the place-names, the confusion of manorial tenures and the transference of the parish from Salisbury diocese to Bath and Wells in 1428. Problems are compounded by parts of the book’s text which jerk from one historical topic to another, often losing the narrative thread in the process and voyaging along more than one tangential cul-se-sac. Despite many references to primary and secondary sources in the form of end-notes, it is sometimes unclear on what evidence a given statement is based. Similarly, some maps are inadequately captioned, and some boundaries they show are questionable.